Noncoronary Vascular Calcification, Bone Mineral Density, and Muscle Mass in Institutionalized Frail Nonagenarians (2017)
The purpose of this study was to compare the vascular calcification in thoracic aorta (TAC), abdominal aorta (AAC), iliac arteries (IAC), and femoral arteries (FAC) and bone mineral density (BMD) of the lumbar vertebrae between frail and robust nonagenarians, as well as to verify the associations between vascular calcification with BMD, muscle tissue quality, and quantity in both groups. Forty-two elderly subjects participated in this study: 29 institutionalized frail (92.0 ± 3.2 years) and 13 robust (89.0 ± 4.0 years) elderly participants. All patients underwent nonenhanced helical thoracic, abdominal, and thigh computed tomography. The frail group presented significantly greater FAC as well as less lumbar BMD than the robust group (p less than 0.05). In the frail group, significant negative relationships were observed between the individual values of FAC with the individual values of BMD (r = -0.35 to -0.43, p less than 0.05) and with the individual values of the quadriceps muscle quantity and quality (r = -0.52, p less than 0.01), whereas no significant relationships were observed in the robust group. The robust group presented less vascular calcification and more BMD in the vertebral bodies than the frail group. In the frail group, femoral artery calcification was significantly negatively correlated with BMD, leg muscle quality, and muscle mass volume. © Mary Ann Liebert, Inc. 2017.